FAKTOR- FAKTOR YANG MEMPENGARUHI TINGKAT PENDAPATAN PEDAGANG KAKI LIMA DI KOTA CIREBON - Ani Sofia Diyani; Karlina Karlina (UIN Siber Syekh Nurjati Cirebon, 2022)
This study aims to analyze and understand the factors that influence the level of income in Cirebon. The variables used are Y variables, namely income, and X variables, capital, length of business, and working hours. This variable was tested using normality, multicollinearity, and heteroscedasticity tests. Then test the data using a t-test and adjusting the coefficient of determination test. The tests carried out present the results that the first hypothesis, namely capital affects income received, where the more capital obtained, the more income received because it is easier to find places and materials or tools to make sales if you have sufficient or excess capital to make sales. Then the variable length of business affects the level of income that will be owned, the reason is that the length of the business will make the workers more agile and more skilled in running the business they have. While on the working hours variable, it is determined that there is no effect on the following variables because the working hours variable is not under the informal sector actors, the existing hours are flexible and sometimes do not match the existing reality. The limitation of this study is that the number of competitors is not included in the opinion of Husaini & Fadhlani (2017) that competitors are more influential than working hours.